Crystal Structure of β-Hexosaminidase B in Complex with Pyrimethamine, a Potential Pharmacological Chaperone() - Bateman, Katherine S. (2011)
[Image: see text] β-Hexosaminidases (β-hex) are a group of glycosyl hydrolase isozymes that break down neutral and sialylated glycosphingolipids in the lysosomes, thereby preventing their buildup in neuronal cells. Some mutants of β-hex have decreased folding stability that results in adult-onset forms of lysosomal storage diseases. However, prevention of the harmful accumulation of glycolipids only requires 10% of wild-type activity. Pyrimethamine (PYR) is a potential pharmacological chaperone that works by stabilizing these mutant enzymes sufficiently to allow more β-hex to arrive in the lysosome, where it can carry out its function. An X-ray structure of the complex between human β-hexosaminidase B (HexB) and PYR has been determined to 2.8 Å. PYR binds to the active site of HexB where several favorable van der Waals contacts and hydrogen bonds are introduced. Small adjustments of the enzyme structure are required to accommodate the ligand, and details of the inhibition and stabilization properties of PYR are discussed.